GENERAL CHARACTERISTICS OF THE WORD-FORMATION SYSTEMS OF THE ENGLISH AND UZBEK LANGUAGES - Mirzayeva Olima Rahmonali qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: This article provides a linguistic analysis of word formation processes in the English and Uzbek languages. The morphological systems of both languages, as well as their similarities and differences in forming new words through affixation, composition, and other methods, are examined. According to the different sources of information, the Uzbek language has an agglutinative nature, whereas English is analytical and partly inflectional, which leads to significant differences in word formation processes. It should be noted that word formation is a process that continuously enriches the vocabulary of a language. There are both similarities and differences between the word formation systems of English and Uzbek. The article explores several methods of word formation and provides numerous examples to clarify the topic